Spectral-element simulations of variable-density turbulent flow in a plane channel - Ryzhenkov Vladimir (EPJ Web of Conferences, 2017)
We perform Large-eddy simulations (LES) of the turbulent flow in a channel with isothermal heated walls with the temperature ratio equal to 2. The variable properties of the fluid are accounted for by using the low Mach number approximation. The Reynolds number based on the bulk velocity, half-width of the channel, density and dynamic viscosity near the cold wall is 6800. We study the effect of spatial resolution on the accuracy of Large-eddy simulations with dynamic Smagorinsky model. The very good agreement of LES results is shown even for the coarse meshes which is attributed to the high accuracy of the spectral method.